The Impact of Radec Method on Literacy Skills and Learning Outcomes of Elementary School Civics Education - Dyahmumpuni, Fenny Ekawati; Sitompul, Nurmida Catherine; Rusmawati, Retno Danu (UNDIKMA, 2026)
This study is motivated by the low literacy skills and Civics (Civic Education) learning outcomes of elementary school students, which are caused by teacher-centered instruction and the limited optimal use of literacy-based strategies and digital media. The research gap arises from the lack of studies implementing strategies that integrate literacy with interactive media. This study aims to examine the effect of the RADEC (Read, Answer, Discuss, Explain, Create) strategy on the literacy skills and Civics learning outcomes of fifth-grade students at SDN Kepanjen 2. Employing a quantitative approach with a quasi-experimental non-equivalent control group design, the study involved an experimental class applying the RADEC strategy and a control class using an expository strategy supported by Canva. The instruments consisted of expert-validated literacy and learning outcome tests. Data were collected through pretests and posttests and analyzed using an Independent Samples t-test and Tests of Between-Subjects Effects with SPSS 27. The results revealed a significant difference between the two groups, with Sig. 0.000 < 0.05 for literacy and t = 5.757 (p = 0.000) for learning outcomes. These findings confirm that the RADEC strategy supported by Canva is effective in improving literacy skills and Civics learning outcomes and is recommended as a 21st-century learning strategy.